Enhancing performance of wall mounted split air conditioner using capillary tube in a tube heat exchanger. Issue 4 (April 2020) - Berman, E T; Komaro, M; Miftakhudin, M; Mutaufiq, M; Suherman, A
Abstract: The high cost of electricity rates has affected the demands of the public for the availability of energy-efficient air conditioning systems. This study aims to obtain data on improving performance of air conditioner using capillary tube in tube heat exchangers. Tests were carried out on a wall mounted split AC capacity of 9000 Btu/h which was modified using a heat exchanger with capillary tube in tube heat exchanger. The results showed that the installation of a capillary tube in tube heat exchanger on a wall mounted split AC resulted in an increase RE and COP of 13.2% and 14.9%, respectively. In addition, the room cooling time in the TiTHX capillary mode testing is shorter. So it has implications for lighter compression work and saves the power consumption required by AC.